ANALISIS PELAYANAN ANTENATAL PADA IBU HAMIL RESIKO TINGGI ANEMIA OLEH BIDAN DESA - Puspitasari, Dian; Wijayanti, SY Trihana (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Klaten District Health Department policy as an effort to reduce maternal deaths due tobleeding is done through training of Normal Childbirth in collaboration with Primary Clinical Training Centre (P2KP) Klaten Regency and midwifery procurement of facilities for handling high-risk antenatal maternal anemia. The purpose of this study is to describe the implementation of aspects of earlydetection, management, counseling, monitoring, recording and reporting on the handling of high riskpregnant women antenatal anemia in Klaten district. Methods: The research is qualitative by using in-depth interviews and direct observation by crosssectional approach. Key informants in this study were six midwives who are dealing with pregnant womenat high risk of anemia and working in Klaten district. Informant triangulation midwife six patients, four headof health center and a head section Klaten District Health Office. The data analysis technique with content analysis includes in-depth interviews with informants processed as analysis of data. Results: The implementation of the antenatal management of pregnant women at high risk of anemia interms of aspects of early detection has met the standard but still there is not yet implemented the measures laboratory hemoglobin and blood type. View from the aspect of management is in conformity with the standard of midwifery. View from the aspect of counseling has not met the standard type of education provided, is not complete, for counseling, child birth preparation anemic pregnant women has not been prepared according to standard P4K and how to deliver the content has not been up to standard. View from the aspect of monitoring not meet the standards re-examination of hemoglobin and Fe tablet compliance with drinking mother has not been implemented according to standards. View from the aspect of recording has complied with the procedures but there are still unfilled column constraints in small-format recording, reporting has not carried out according to the procedure. Conclusion: Suggestion that the Klaten district health offices to increase co-operation with IBI professional organizations to jointly uphold the application of Standard Operating Procedures, conductrefres her antenatal treatment of anemia of pregnant women, improving the format of recording andreporting of pregnant women at high risk of anemia. Key words: Antenatal care of pregnant women at high risk of anemia, the village midwife